STRATEGI PENINGKATAN KUALITAS PRODUK KEMASAN AMDK BERBASIS METODE SIX SIGMA DAN QFD - Resma Dwi Santika; Lithrone Laricha Salomon; Carla Olyvia Doaly (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2025)
Increasingly fierce industrial competition requires companies to continuously improve the quality of their products to meet customer expectations and maintain competitiveness. This research was conducted at PT XYZ, a manufacturing company that produces Bottled Drinking Water (AMDK), with a focus on cup packaging products. The purpose of this research is to identify the types and causes of product defects, and formulate a quality improvement strategy using the Six Sigma method based on the DMAIC (Define, Measure, Analyze, Improve, Control) and Quality Function Deployment (QFD) approaches. The observation results show that the dominant types of defects are frosted cups, mushy cups, striped cups, and cup sizes that exceed the standard. The Defect per Million Opportunities (DPMO) calculation shows a value of 5.755 with a sigma level of 4, which means that the production process still requires significant improvement to achieve the Six Sigma target. Through the QFD stage, customer requirements are translated into technical characteristics that form the basis for the development of the House of Quality (HoQ). The results of this study provide a quality improvement strategy that is more structured and oriented to customer needs, and can be used as a reference for continuous improvement in the mineral water industry.